2017
DOI: 10.1177/1747493017694391
|View full text |Cite
|
Sign up to set email alerts
|

2014 Chinese guidelines for secondary prevention of ischemic stroke and transient ischemic attack

Abstract: Ischemic stroke and transient ischemic attack (TIA) are the most common cerebrovascular disorder and leading cause of death in China. The Effective secondary prevention is the vital strategy for reducing stroke recurrence. The aim of this guideline is to provide the most updated evidence-based recommendation to clinical physicians from the prior version. Control of risk factors, intervention for vascular stenosis/occlusion, antithrombotic therapy for cardioembolism, and antiplatelet therapy for noncardioemboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 172 publications
0
70
0
Order By: Relevance
“…The Chinese clinical guidelines for the secondary prevention of ischaemic stroke and TIA recommend an optimal dosage of aspirin between 75 mg/day and 150 mg/day. A combination of aspirin and clopidogrel for 21 days is recommended for patients with minor stroke or high-risk TIA within 24 hour of onset [ 10 ]. These recommendations are based on the CHANCE trial [ 11 ].…”
Section: First Session—update On Cardiovascular Disease and Stroke: Ementioning
confidence: 99%
“…The Chinese clinical guidelines for the secondary prevention of ischaemic stroke and TIA recommend an optimal dosage of aspirin between 75 mg/day and 150 mg/day. A combination of aspirin and clopidogrel for 21 days is recommended for patients with minor stroke or high-risk TIA within 24 hour of onset [ 10 ]. These recommendations are based on the CHANCE trial [ 11 ].…”
Section: First Session—update On Cardiovascular Disease and Stroke: Ementioning
confidence: 99%
“…[ 2 ] The combination of aspirin and clopidogrel within 24 h of an AMIS/TIA and continuation for 21 days was recommended according to the latest Chinese and American guidelines for the secondary prevention of stroke. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…1,3,20,21 In recent years, with the development of imaging, radiographic abnormality in evaluating the risk of stroke after TIA is more and more important significance.…”
Section: Abcd2i Scorementioning
confidence: 99%
“…1 To date, increased incidence of TIA is observed from 18% of people aged 45 and above and who at least experienced at least one TIA. 2 Reports suggested that percentages of other TIAs occurring within 7 d after cerebral infarction rate reach as high as 8.0% to 10.5%, whereas the incidence of 90 d is 10.5% -14.6%, and the possibility of serious incidence (such as death and asymptomatic cerebral infarction, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation